IDENTIFICATION OF CHEMICAL COMPOUNDS ETHANOL EXTRACT LEAF MIMOSA THAT GROWS IN DENPASAR CITY - Wiadnyani, Kadek Ayu; Dharmayudha, Anak; Sudimartini, Luh Made; Merdana, I Made (Buletin Veteriner Udayana, 2024)
Indonesia is a tropical country rich in natural resources including medicinal plants, which have been used as traditional medicines for generations. Mimosa (Mimosa pudica L.) is a plant that has a lot of potential to be developed into raw materials for traditional medicine because it has many pharmacological activities that are beneficial in supporting health. This study aims to determine the active phytochemical compounds contained in the ethanol extract of Mimosa leaves. Mimosa leaves will be collected around the city of Denpasar, Bali. The sample will then be extracted using 70% ethanol solvent by maceration method. Phytochemical tests which include steroid/triterpenoid tests, flavonoid tests, alkaloid tests, phenolic tests, tannin tests, and saponin tests were carried out to identify the active phytochemical compounds in the samples. The data obtained were analyzed descriptively qualitatively. Based on testing of the phytochemical compounds of the 70% ethanol extract of mimosa leaves grown in the city of Denpasar, it was concluded that the extract contains triterpenoid/steroidal, alkaloids, flavonoids, phenolics, tannins, and saponins. This research is an early stage in detecting the content of secondary metabolites in mimosa. Further research is suggested to be carried out in testing the content of mimosa leaves, for example fractionation, which can later be used in practical applications in the field of veterinary medicine.